Study Of The Impact Of The Information Technology And Communication Technology On The Experience Of Work In The Multinational Electrical And Electronic Manufacturing Companies - Nagappan, Chettiar Rengasamy (2003)
Essentially, the current study attempted to examine the causal or dependence relationships of technology induced work characteristics and objective of management on job related tension, job satisfaction, and organizational commitment based on the strength of their empirical exposition for the work groups of operative, administrative, and technical. Research results showed that the information and communication technology did inject new characteristics into the work and work organization.